Studying Special Strength Relationship and Performance Level Contribution In Some Skills of Vault and Uneven Bars In Artistic Gymnastics For Women In Sophomore Students - Shehab, Zahra; Yousif, Hamed (Journal of Physical Education, 2020)
The research aimed at identifying the values of special strength variables and skill performance of some vault and uneven bars’ skills in sophomore college students of physical education & Sport Sciences as well as identifying the correlation relationship and contribution of special strength with the performance level of some vaulting and uneven bars skills. The researchers hypothesized a statistical relationship between special strength and uneven bar skills, a statistical correlation between special strength and value, and finally and contribution between special strength and research variables. The subjects were (14) sophomore students, a pilot study, as well as many tests, physical abilities, and skills were all conducted to conclude that the contribution of special strength with performance level on vault and uneven bars was weak while abs endurance strength have a significant contribution on open jump. Finally, the researchers recommended studying the weaknesses in performing women’s artistic gymnastics skills through identifying contributions and special strength development.